2018
DOI: 10.2147/idr.s181124
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistance profiling and transmission dynamics of multidrug-resistant <em>Mycobacterium tuberculosis</em> in Saudi Arabia revealed by whole genome sequencing

Abstract: BackgroundIn Saudi Arabia, cross-border transmission of multidrug-resistant (MDR) Mycobacterium tuberculosis complex (MTBC) strains might be particularly fostered by high immigration rates. Herein, we aimed to elucidate the transmission dynamics of MDR-MTBC strains and reveal a detailed prediction of all resistance-conferring mutations for the first- and second-line drugs.MethodsWe investigated all MDR-MTBC strains collected between 2015 and 2017 from provincial mycobacteria referral laboratories and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…The authors concluded that the healthcare worker had contacted the infection from a patient that displayed nearly identical mutation and MIRU-VNTR patterns. More elaborate sequence comparisons derived from WGS or cgMLST have also identified transmission of infection in low-TB-incidence settings [5961].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the healthcare worker had contacted the infection from a patient that displayed nearly identical mutation and MIRU-VNTR patterns. More elaborate sequence comparisons derived from WGS or cgMLST have also identified transmission of infection in low-TB-incidence settings [5961].…”
Section: Discussionmentioning
confidence: 99%
“…Older studies have used blunt genotyping tools (e.g., IS 6110 restriction fragment length polymorphism, spoligotyping, and mycobacterial interspersed repetitive unit–variable-number tandem-repeat) with limited or convenient sample sizes. DR TB studies using WGS in Saudi Arabia and Portugal have revealed transmission clusters of MDR TB; however, they had small samples and provided limited data on epidemiologic links ( 36 , 37 ). Extrapolating from our findings, primary-resistant TB strains may be the main contributors to the current global problem of high MDR TB and XDR TB prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of key characteristics of included studies is shown in table 1 (further detail in appendix 2 ). 1 , 19 130 Studies were classified into four themes based on their overall aims (these themes were not mutually exclusive): transmission (n=82), evolution (n=36), strain identification (n=11), and clinical outcomes (n=2; appendix 1 p 5). The number of patients was missing for 21 (18%) articles.…”
Section: Resultsmentioning
confidence: 99%